A chopped fiber reinforced ultra-high temperature ceramic matrix composite material and preparation method thereof
By using chopped fibers to react and hot-press sintering with materials such as silicon borosity and oxygen, the existing fiber-reinforced ultra-high temperature ceramic matrix composites have been solved, and the effects of high density, low porosity, excellent mechanical properties and simplified process are achieved.
Patent Information
- Application Number
- CN202410687951.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-05-30
AI Technical Summary
The existing fiber-reinforced ultra-high temperature ceramic matrix composites have poor oxidation resistance in high-temperature environments, large differences in mechanical properties, and complex preparation processes, making them not suitable for large-scale industrial production.
The composite material obtained is heat-pressed and sintered by chopped fibers and mixed powders composed of silicon boron-oxynitride, pure silicon powder, zirconium diboride and carbon source.
It improves the density and mechanical properties of composite materials, simplifies the preparation process, is suitable for large-scale industrial production, and shows better anti-oxidation properties in high-temperature environments.
Smart Images

Figure CN118666586B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic-based composite materials, and in particular relates to a chopped fiber reinforced ultra-high temperature ceramic-based composite material and a preparation method thereof. Background Art
[0002] Ultra-high temperature ceramic materials have high melting points, high stability, and excellent mechanical properties. Therefore, they can be used as thermal protection materials for aircraft to ensure that aircraft can operate stably under extreme temperatures and extreme environments. However, pure ultra-high temperature ceramics have poor toughness and thermal shock resistance, and are prone to brittle fracture under conditions of rapid heating or cooling. Fiber-reinforced ultra-high temperature ceramic-based composites are composite materials with fiber materials as reinforcements and ultra-high temperature ceramics as the matrix. The addition of reinforcements can strengthen and toughen ultra-high temperature ceramics to meet the application needs of ultra-high temperature ceramics in the field of aerospace thermal protection materials.
[0003] The preparation methods of fiber-reinforced ultra-high temperature ceramic matrix composite materials are mainly precursor impregnation pyrolysis, chemical vapor deposition, mechanical alloying combined with hot pressing sintering, etc. Among them, the chemical vapor deposition method has low deposition efficiency, long preparation cycle, and high equipment requirements; the precursor impregnation pyrolysis method can obtain composite materials with excellent mechanical properties at a lower preparation temperature, but the impregnation efficiency is low, the density of the composite material is low, there are many pores, and multiple cycles of impregnation pyrolysis make the production preparation cycle too long, and there is a disadvantage of low ceramic conversion rate. The mechanical alloying combined with hot pressing sintering method greatly reduces the open pores of the composite material through pressure-assisted sintering, but the amorphous powder prepared by mechanical alloying is difficult to impregnate the carbon fiber preform, and the process is complicated, the equipment requirements are high, the production efficiency is low, which is not conducive to large-scale industrial production, and its sintering temperature is extremely high, which makes the ultra-high temperature ceramic matrix corrode and damage the carbon fiber, reducing the strengthening and toughening effect of the fiber on the composite material.
[0004] There is a patent that uses silicon, boron, oxygen and nitrogen as inorganic precursors to prepare slurry. After continuous carbon fiber is impregnated with slurry, it is wound, spread, and naturally dried to obtain fiber layers, which are loaded into molds and subjected to reaction hot pressing and sintering in a vacuum hot pressing furnace to convert silicon, boron, oxygen and nitrogen into silicon, boron, carbon and nitrogen ultra-high temperature composite ceramics. Compared with other methods, this method only requires one impregnation and drying, which shortens the production cycle; improves the density of the composite material; and only requires a lower sintering temperature to obtain a composite material with excellent performance. However, the fiber-reinforced ultra-high temperature ceramic-based composite material prepared by this method has poor antioxidant properties; the mechanical properties in different directions vary greatly; and during the preparation process, the powder needs to be mixed with water and evenly dispersed in water to make a slurry, and the continuous fiber needs to be impregnated. After impregnation, winding, spreading, cutting and other operations are required. The preparation process is complicated and not suitable for large-scale industrial production. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a short-fiber reinforced ultra-high temperature ceramic-based composite material and a preparation method thereof. A mixed powder consisting of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source and short-fibers are used as preparation raw materials, and a reaction hot pressing sintering process is adopted. The obtained composite material has higher density and lower porosity, and the flexural strength and oxidation resistance of the composite material are improved. The preparation method has fewer production steps, a simple production process, and a short process flow, and is suitable for large-scale industrial production.
[0006] In order to solve the above problems, one aspect of the present invention provides a chopped fiber reinforced ultra-high temperature ceramic matrix composite material: its preparation raw materials include mixed powder and chopped fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and carbon source is 35-45:12-20:18-27:18-25.
[0007] Preferably, the mass ratio of silicon boron oxygen nitrogen, pure silicon powder, zirconium diboride and carbon source is 38-41:14-17:22-24:20-23.
[0008] Preferably, the mass ratio of the mixed powder to the chopped fibers is 85-87:13-15.
[0009] Preferably, the chopped fibers are chopped carbon fibers; the length of the chopped carbon fibers is 2-20 mm.
[0010] Preferably, the carbon source is a mixture of carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 38-41:14-17:22-24:13-15:7-8.
[0011] Another aspect of the present invention provides a method for preparing the above-mentioned chopped fiber reinforced ultra-high temperature ceramic matrix composite material, comprising the following steps:
[0012] S1. Dry-mixing silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, a carbon source and the chopped fibers to obtain a composite raw material;
[0013] S2. The composite raw material is placed into a mold for hot pressing and sintering to obtain the chopped fiber reinforced ultra-high temperature ceramic matrix composite material.
[0014] Preferably, step S1 specifically includes the following steps:
[0015] Firstly, silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source are ball-milled and mixed to obtain a mixed powder; then, the mixed powder is stirred and mixed with the chopped fibers to obtain the composite raw material.
[0016] Preferably, the mixing time of the ball milling is 3 to 4 hours, the material-ball ratio is 1:30 to 1:60, and the rotation speed is 120 to 160 rpm.
[0017] Preferably, the stirring and mixing time is 8 to 12 hours.
[0018] Preferably, the hot pressing sintering is specifically: in a vacuum atmosphere, heating to 1500-1800° C. at a rate of 5-10° C. / min, and then keeping the temperature at a uniaxial pressure of 20-40 MPa for 1-2 hours.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The short-cut fiber reinforced ultra-high temperature ceramic matrix composite material of the present invention uses silicon boron oxygen nitrogen as an inorganic precursor, and the inorganic precursor can react chemically with a carbon source at high temperature. The silicon boron oxygen nitrogen inorganic precursor reacts with the carbon source to generate carbon dioxide, and the excess unreacted carbon source forms a silicon boron carbon nitrogen matrix with the remaining silicon, boron and nitrogen. Zirconium boride can react with oxygen to generate zirconium dioxide, which is compounded in the matrix to improve the high temperature performance of the composite material. Silicon boron oxygen nitrogen is converted into silicon boron carbon nitrogen ultra-high temperature composite ceramics through a carbon reduction reaction, and the silicon boron oxygen nitrogen precursor can be softened in a temperature range of 1300 to 1700°C, and has fluidity when pressurized after softening, and can better penetrate the reinforcing fiber, thereby improving the density of the fiber reinforced ceramic matrix composite blank. Therefore, a densified (porosity less than 5%) carbon fiber reinforced high temperature ceramic matrix composite material can be obtained under low temperature and short cycle conditions.
[0021] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of the present invention is prepared by adding pure silicon powder and an excess of carbon source. While reacting to generate a silicon-boron-carbon-nitrogen high temperature ceramic matrix, the silicon powder and the carbon source further react to generate nanocrystalline silicon carbide. The silicon carbide grains generated by the reaction are small and are easy to sinter and densify. The mechanical properties and high temperature oxidation resistance of the composite material can be improved while the density is improved. The reinforcing fibers are chopped fibers. Compared with the longer oxidation channels generated when the continuous fibers are oxidized, the oxidation channels generated after the chopped fibers are oxidized are shorter, which can block the composite material from being further oxidized. Therefore, compared with the continuous fiber composite material, the chopped fiber composite material has better high-temperature oxidation resistance. In addition, the mechanical properties of the continuous fiber reinforced composite material in each direction are different. The mechanical properties along the continuous direction of the continuous fiber are good, and the mechanical properties perpendicular to the continuous direction are poor. After the chopped fibers are compounded with the ceramic matrix, they are randomly scattered in the matrix, so that the mechanical properties of the composite material in each direction are strengthened and toughened, and the mechanical properties of the composite material in each direction are close. When the continuous fiber is compounded with the silicon boron oxygen nitrogen precursor, the silicon boron oxygen nitrogen powder needs to be made into a slurry and impregnated. After the impregnation is completed, winding, spreading, cutting and other operations are required, while the chopped fibers only need to be mixed with the silicon boron oxygen nitrogen powder. Therefore, the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of the embodiment of the present invention has a shorter production process, higher production efficiency, and low equipment requirements in the entire process, which is suitable for large-scale production in industry.
[0022] Compared with the mechanical alloying combined with hot pressing and sintering method, the preparation method of the short-cut fiber reinforced ultra-high temperature ceramic-based composite material of the present invention has a simpler powder mixing process, low equipment requirements, low production cost and short production cycle; compared with the precursor impregnation and cracking method, it can shorten the production cycle by 30-50%, reduce pollution in industrial production, and obtain a high-density composite material with high density through a reaction hot pressing process, thereby improving the oxidation resistance of the product; compared with the use of continuous carbon fiber strengthening and toughening, short-cut fibers are used as reinforcing materials, and there is no need to make the powder into a slurry for impregnation of the fiber. The powder and the short-cut fibers can be directly dry-mixed, and there is no need to wind, spread or cut the fibers. The process flow is simple and the cycle is short. The composite material matrix and the segmented fibers are more tightly combined, so that the porosity of the composite material is small, and the oxidation resistance of the composite material is improved, thereby improving the reliability of the application of ultra-high temperature ceramics in high temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a scanning electron microscope photograph of a cross section of the chopped fiber reinforced ultrahigh temperature ceramic matrix composite material obtained in Example 1 of the present invention after a three-point bending test;
[0024] Figure 2is a scanning electron microscope photograph of a cross section of the chopped fiber reinforced ultrahigh temperature ceramic matrix composite material obtained in Example 1 of the present invention after a three-point bending test;
[0025] Figure 3 is a scanning electron microscope photograph of a cross section of the chopped fiber reinforced ultrahigh temperature ceramic matrix composite material obtained in Example 1 of the present invention after a three-point bending test;
[0026] Figure 4 This is a surface scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation experiment;
[0027] Figure 5 This is a surface scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation experiment;
[0028] Figure 6 This is a surface scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation experiment;
[0029] Figure 7 This is a cross-sectional scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation test;
[0030] Figure 8 This is a cross-sectional scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation test;
[0031] Fig. 9 This is a cross-sectional scanning electron microscope image of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Example 1 of the present invention after an oxidation test;
[0032] Fig.10 This is an X-ray electron diffraction phase analysis spectrum of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material obtained in Examples 1, 2, and 3 of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] One aspect of an embodiment of the present invention provides a chopped fiber reinforced ultra-high temperature ceramic matrix composite material, the preparation raw materials of which include a mixed powder and chopped fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and carbon source is 35-45:12-20:18-27:18-25.
[0035] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of the embodiment of the present invention uses silicon boron oxygen nitrogen as an inorganic precursor, which can react chemically with a carbon source at high temperature. The silicon boron oxygen nitrogen inorganic precursor reacts with the carbon source to generate carbon dioxide, and the excess unreacted carbon source reacts with the remaining silicon, boron, and nitrogen to form a silicon boron carbon nitrogen matrix. Zirconium boride can react with oxygen to generate zirconium dioxide, which is compounded in the matrix to improve the high temperature performance of the composite material. Silicon boron oxygen nitrogen is converted into silicon boron carbon nitrogen ultra-high temperature composite ceramics through carbon reduction reaction, and the silicon boron oxygen nitrogen precursor can be softened in the temperature range of 1300 to 1700 ° C. After softening, it has fluidity when pressurized, and can better penetrate the reinforcing fiber, thereby improving the density of the fiber reinforced ceramic matrix composite blank. Therefore, a densified (porosity less than 5%) carbon fiber reinforced high temperature ceramic matrix composite material can be obtained under low temperature and short cycle conditions.
[0036] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of the embodiment of the present invention is prepared by adding pure silicon powder and an excess of carbon source. While reacting to form a silicon-boron-carbon-nitrogen high temperature ceramic matrix, the silicon powder and the carbon source further react to form nanocrystalline silicon carbide. The silicon carbide grains formed by the reaction are small and easy to sinter and densify. The density can be improved while the mechanical properties and high temperature oxidation resistance of the composite material can be improved. The reinforcing fibers are chopped fibers. Compared with the longer oxidation channels generated when the continuous fibers are oxidized, the oxidation channels generated after the chopped fibers are oxidized are shorter, which can block the composite material from being further oxidized. Therefore, compared with the continuous fiber composite material, the chopped fiber composite material has better high-temperature oxidation resistance. In addition, the mechanical properties of the continuous fiber reinforced composite material in each direction are different. The mechanical properties along the continuous direction of the continuous fiber are good, and the mechanical properties perpendicular to the continuous direction are poor. After the chopped fibers are compounded with the ceramic matrix, they are randomly scattered in the matrix, so that the mechanical properties of the composite material in each direction are strengthened and toughened, and the mechanical properties of the composite material in each direction are close. When the continuous fiber is compounded with the silicon boron oxygen nitrogen precursor, the silicon boron oxygen nitrogen powder needs to be made into a slurry and impregnated. After the impregnation is completed, winding, spreading, cutting and other operations are required, while the chopped fibers only need to be mixed with the silicon boron oxygen nitrogen powder. Therefore, the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of the embodiment of the present invention has a shorter production process, higher production efficiency, and low equipment requirements in the entire process, which is suitable for large-scale production in industry.
[0037] Among them, the adjustment of the mass ratio of silicon boron oxygen nitrogen, pure silicon powder, zirconium diboride, and carbon source will significantly affect the mechanical properties and antioxidant properties of the composite material. To this end, the embodiment of the present invention further optimizes the ratio of raw materials. Preferably, the mass ratio of silicon boron oxygen nitrogen, pure silicon powder, zirconium diboride, and carbon source is 38-41:14-17:22-24:20-23. At this mass ratio, the short-cut fiber reinforced ultra-high temperature ceramic matrix composite material can have better mechanical properties and antioxidant properties, and improve the reliability of ultra-high temperature ceramics in high temperature environments.
[0038] Among them, the mass ratio of the mixed powder to the chopped fibers is not arbitrarily selected. If the content of the chopped fibers is too high, the fibers will agglomerate and bridge in the matrix, which will reduce the mechanical properties of the composite material. If the content of the chopped fibers is too low, the effect of the fibers as a reinforcing phase in the composite material will be weakened, that is, the mechanical properties will hardly be improved. Taking the above effects into consideration, preferably, the mass ratio of the mixed powder to the chopped fibers is 80-90:10-20. Further preferably, the mass ratio of the mixed powder to the chopped fibers is 85-87:13-15.
[0039] The specific fiber type of the chopped fibers can be adjusted according to product requirements. Preferably, the chopped fibers are chopped carbon fibers.
[0040] The length of the chopped carbon fiber can be adjusted according to product requirements, but the length of the chopped carbon fiber will also affect the performance of the composite material. If the chopped carbon fiber is too short, the toughening effect is poor, and if the chopped carbon fiber is too long, the mixing uniformity with the mixed powder is poor. Considering the above effects, preferably, the length of the chopped carbon fiber is 2-20 mm.
[0041] Preferably, the carbon source is a mixture of carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 38-41:14-17:22-24:13-15:7-8.
[0042] Another aspect of an embodiment of the present invention provides a method for preparing the above-mentioned chopped fiber reinforced ultra-high temperature ceramic matrix composite material, comprising the following steps:
[0043] S1. Dry-mixing silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, a carbon source and the chopped fibers to obtain a composite raw material;
[0044] S2. The composite raw material is placed into a mold for hot pressing and sintering to obtain the chopped fiber reinforced ultra-high temperature ceramic matrix composite material.
[0045] The preparation method of the chopped fiber reinforced ultra-high temperature ceramic matrix composite material in the embodiment of the present invention has a simpler powder mixing process, low equipment requirements, low production cost and short production cycle compared to the mechanical alloying combined with hot pressing and sintering method; compared to the precursor impregnation and cracking method, it can shorten the production cycle by 30 to 50%, reduce pollution in industrial production, and obtain a high-density composite material with high density through a reaction hot pressing process, thereby improving the oxidation resistance of the product; compared to the use of continuous carbon fiber strengthening and toughening, chopped fibers are used as reinforcing materials, and there is no need to make the powder into a slurry for impregnation of the fiber. The powder and the chopped fibers can be directly dry mixed, and there is no need to wind, spread or cut the fibers. The process flow is simple and the cycle is short, and the composite matrix and the segmented fibers are more tightly combined, so that the porosity of the composite material is small, and the oxidation resistance of the composite material is improved, thereby improving the reliability of the application of ultra-high temperature ceramics in high temperature environments.
[0046] In some embodiments, the dry mixing can be performed by ball milling, stirring, kneading and other dry mixing methods.
[0047] Preferably, step S1 specifically includes the following steps:
[0048] Firstly, silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source are ball-milled and mixed to obtain a mixed powder; then, the mixed powder is stirred and mixed with the chopped fibers to obtain the composite raw material.
[0049] Preferably, the mixing time of the ball milling is 3 to 4 hours, the material-ball ratio is 1:30 to 1:60, and the rotation speed is 120 to 160 rpm.
[0050] Preferably, the stirring and mixing time is 8 to 12 hours.
[0051] Preferably, the hot pressing sintering is specifically: in a vacuum atmosphere, heating to 1500-1800° C. at a rate of 5-10° C. / min, and then keeping the temperature at a uniaxial pressure of 20-40 MPa for 1-2 hours.
[0052] In the following embodiments, silicon boron oxide and nitrogen can be prepared by the method disclosed in the Chinese patent document with publication number CN 105541340 B and patent name Nitride ceramic-microcrystalline glass composite material and preparation method thereof.
[0053] Example 1
[0054] The short-cut fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is prepared from raw materials including mixed powder and short-cut carbon fiber; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 40:16:23:14:7; in the preparation raw materials, the mass content of short-cut carbon fiber is 14%, and the mass content of mixed powder is 86%. The length of the short-cut carbon fiber is 2-20 mm.
[0055] The method for preparing the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment comprises the following steps:
[0056] 1. Silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite were mixed according to the above mass ratio, and dry-mixed and ball-milled for 3 hours to obtain a mixed powder; the material-to-ball ratio of the ball mill was 1:40, and the rotation speed was 150 rpm.
[0057] 2. The mixed powder and the chopped carbon fibers were mixed according to the above mass percentages, and stirred and mixed in a forced mixer for 10 hours to uniformly disperse the mixed powder and the carbon fibers to obtain a composite raw material.
[0058] 3. The composite raw material is loaded into a hot pressing sintering mold, and after vacuuming, the temperature is raised to 1700°C at a rate of 5°C / min, and hot pressing sintering is performed under a uniaxial pressure of 20 MPa for 2 hours. After the hot pressing sintering is completed and the furnace is cooled, the short fiber reinforced ultra-high temperature ceramic matrix composite material is obtained by demolding the mold.
[0059] Example 2
[0060] The short-cut fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is prepared from raw materials including mixed powder and short-cut carbon fiber; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 38:17:24:13:8; in the preparation raw materials, the mass content of short-cut carbon fiber is 14%, and the mass content of mixed powder is 86%. The length of the short-cut carbon fiber is 2-20 mm.
[0061] The method for preparing the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment comprises the following steps:
[0062] 1. Silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite were mixed according to the above mass ratio, and dry-mixed and ball-milled for 3 hours to obtain a mixed powder; the material-to-ball ratio of the ball mill was 1:60, and the rotation speed was 120 rpm.
[0063] 2. The mixed powder and the chopped carbon fiber are mixed according to the above mass percentage, and stirred and mixed for 12 hours in a forced mixer to uniformly disperse the mixed powder and the carbon fiber to obtain a composite raw material.
[0064] 3. The composite raw material is loaded into a hot pressing sintering mold, and after vacuuming, the temperature is raised to 1600°C at a rate of 5°C / min, and hot pressing and sintering is performed under a uniaxial pressure of 30 MPa for 2 hours. After the hot pressing and sintering is completed and the furnace is cooled, the short fiber reinforced ultra-high temperature ceramic matrix composite material is obtained by demolding the mold.
[0065] Example 3
[0066] The short-fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is prepared from raw materials including mixed powder and short-cut carbon fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 41:14:22:15:8; in the preparation raw materials, the mass content of short-cut carbon fibers is 14%, and the mass content of mixed powder is 86%. The length of the short-cut carbon fibers is 2-20 mm.
[0067] The method for preparing the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment comprises the following steps:
[0068] 1. Silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite were mixed according to the above mass ratio, and dry-mixed and ball-milled for 3 hours to obtain a mixed powder; the material-to-ball ratio of the ball mill was 1:30, and the rotation speed was 160 rpm.
[0069] 2. The mixed powder and the chopped carbon fibers were mixed according to the above mass percentages, and stirred and mixed in a forced mixer for 8 hours to uniformly disperse the mixed powder and the carbon fibers to obtain a composite raw material.
[0070] 3. The composite raw material is loaded into a hot pressing sintering mold, and after vacuuming, the temperature is raised to 1500°C at a rate of 5°C / min, and hot pressing sintering is performed under a uniaxial pressure of 30 MPa for 2 hours. After the hot pressing sintering is completed and the furnace is cooled, the short fiber reinforced ultra-high temperature ceramic matrix composite material is obtained by demolding the mold.
[0071] Example 4
[0072] The short fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is prepared from raw materials including mixed powder and short chopped carbon fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 35:20:27:12:6; in the preparation raw materials, the mass content of short chopped carbon fibers is 14%, and the mass content of mixed powder is 86%. The length of the short chopped carbon fibers is 2-20 mm. The preparation method of the short fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is the same as that of Example 1.
[0073] Example 5
[0074] The short fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is prepared from raw materials including mixed powder and short chopped carbon fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 45:12:18:16:9; in the preparation raw materials, the mass content of short chopped carbon fibers is 14%, and the mass content of mixed powder is 86%. The length of the short chopped carbon fibers is 2-20 mm. The preparation method of the short fiber reinforced ultra-high temperature ceramic matrix composite material of this embodiment is the same as that of Example 1.
[0075] Example 6
[0076] The composition and mass ratio of the mixed powder of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment are the same as those of Example 1, except that the mass content of the short-cut carbon fiber in the preparation raw material is 13%, and the mass content of the mixed powder is 87%. The preparation method of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment is the same as that of Example 1.
[0077] Example 7
[0078] The composition and mass ratio of the mixed powder of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment are the same as those of embodiment 1, except that the mass content of the short-cut carbon fiber in the preparation raw material is 15%, and the mass content of the mixed powder is 85%. The preparation method of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment is the same as that of embodiment 1.
[0079] Example 8
[0080] The composition and mass ratio of the mixed powder of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment are the same as those of Example 1, except that the mass content of the short-cut carbon fiber in the preparation raw material is 10%, and the mass content of the mixed powder is 90%. The preparation method of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment is the same as that of Example 1.
[0081] Example 9
[0082] The composition and mass ratio of the mixed powder of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment are the same as those of Example 1, except that the mass content of the short-cut carbon fiber in the preparation raw material is 20%, and the mass content of the mixed powder is 80%. The preparation method of the short-cut fiber reinforced ultrahigh temperature ceramic matrix composite material of this embodiment is the same as that of Example 1.
[0083] Comparative Example 1
[0084] This comparative example is a continuous carbon fiber reinforced ultrahigh temperature ceramic matrix composite material, and its preparation raw materials include mixed powder and continuous carbon fiber; the composition and mass ratio of the mixed powder are the same as those in Example 1, and the preparation method of the composite material includes the following steps:
[0085] 1. 40g of 40:16:23:14:7 silicon boron oxide nitrogen powder, 16g of pure silicon powder, 23g of zirconium diboride, 14g of carbon black, and 7g of flake graphite were ball-milled for 3 hours with 210ml of deionized water as the medium, and then 3ml of Triton, 3ml of polyethylene glycol, and 1.55g of methyl cellulose were added, and the ball milling was continued for 3 hours to obtain a slurry. The ball-to-material ratio was 1:40, and the rotation speed was 150 rpm.
[0086] 2. After the continuous carbon fiber (T300) is impregnated with the slurry, it is wound, spread and naturally dried to form a carbon fiber layer impregnated with ultra-high temperature ceramic powder.
[0087] 3. Cut the carbon fiber plies into 60mm×40mm, cross-stack them in the 0° and 90° directions, load them into the mold and evacuate them, then heat them to 1200℃ at a rate of 10℃ / min, and then heat them to 1700℃ at a rate of 5℃ / min, and heat them for 0.5h at 1700℃ and 20MPa for hot pressing sintering. After the hot pressing sintering is completed and the furnace is cooled, it is removed from the furnace and demolded to obtain a continuous carbon fiber reinforced ultra-high temperature ceramic matrix composite material.
[0088] Comparative Example 2
[0089] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this comparative example is different from that of Example 1 in that pure silicon powder is not added, and the other components, mass ratios and preparation methods are the same as those of Example 1.
[0090] Comparative Example 3
[0091] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this comparative example is different from that of Example 1 in that the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite in the mixed powder is 32:23:29:10:6. The rest is the same as that of Example 1.
[0092] Comparative Example 4
[0093] The chopped fiber reinforced ultra-high temperature ceramic matrix composite material of this comparative example is different from that of Example 1 in that the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite in the mixed powder is 47:10:15:18:10. The rest is the same as that of Example 1.
[0094] The density, open porosity, flexural strength, fracture toughness and oxidation weight loss rate of the composite materials obtained from the above-mentioned embodiments and comparative examples were measured. The density and open porosity were measured by the Archimedean drainage method; the flexural strength was measured by the three-point bending method; the oxidation weight loss rate was measured by keeping the temperature at 1500°C for 24 hours in a high-temperature box furnace under air atmosphere. The test results are shown in Table 1 below. It can be seen from the data in Table 1 below that the continuous carbon fiber reinforced ultra-high temperature ceramic matrix composite material of Comparative Example 1 has poor antioxidant properties, and the mechanical properties of the composite material in different directions vary greatly; in the chopped fiber reinforced ultra-high temperature ceramic matrix composite material of Comparative Example 2, pure silicon powder was not added, and its antioxidant properties were poor; compared with the embodiments of the present application, the mass ratio of the components in the mixed powder of Comparative Examples 3 and 4 is inappropriate, and the comprehensive performance of the material is not as good as that of the embodiments.
[0095] In each embodiment of the present invention, the mass ratios of the components in the mixed powders in embodiments 1-5 are different, among which the composite materials of embodiments 1-3 have better comprehensive performances of mechanical properties and antioxidant properties, and are preferred embodiments. Compared with embodiments 6-9, the difference in embodiment 1 is that the mass ratios of the mixed powders and the chopped carbon fibers are different, and the comprehensive performances of embodiments 1, 6, and 7 are better, which are better than embodiments 8 and 9, and are preferred embodiments.
[0096] like Figure 1-3 The scanning electron microscope photograph of the cross section of the composite material obtained in Example 1 after the three-point bending test is shown in FIG. Figure 1-3 It can be seen that the chopped fibers are evenly dispersed in the ultra-high temperature ceramic matrix, ensuring the uniform performance of the composite material. The composite material exhibits high density and no obvious holes are observed. Figure 4-6 This is a surface scanning electron microscope image of the composite material obtained in Example 1 after oxidation experiment. Figure 4-6 It can be seen that after oxidation, the surface of the composite material is covered with a uniform glass phase oxide layer, which protects the composite material and reduces oxidation damage. Figure 7-9 This is a cross-sectional scanning electron microscope image of the composite material obtained in Example 1 after oxidation experiment. Figure 7-9 It can be seen that after the composite material is oxidized, the glass phase protective layer is overall thinner and the oxidation loss is smaller, and the ultra-high temperature ceramic matrix and chopped carbon fibers under the protective layer do not experience a strong oxidation effect. Fig.10 The X-ray electron diffraction phase analysis spectra of the composite materials of Examples 1, 2 and 3 show that the phase composition of the composite materials is SiC, BN, ZrB 2 、ZrO 2 , ZrC.
[0097] Table 1
[0098]
[0099]
[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A chopped fiber reinforced ultra-high temperature ceramic matrix composite material, characterized in that: The preparation raw materials include mixed powder and chopped fibers; the mixed powder includes silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and carbon source is 38-41:14-17:22-24:20-23; the mass ratio of the mixed powder to the chopped fibers is 85-87:13-15; the chopped fibers are chopped carbon fibers; the length of the chopped carbon fibers is 2-20 mm.
2. The chopped fiber reinforced ultra-high temperature ceramic matrix composite material according to claim 1, characterized in that: The carbon source is a mixture of carbon black and flake graphite; the mass ratio of silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, carbon black and flake graphite is 38-41:14-17:22-24:13-15:7-8.
3. A method for preparing the chopped fiber reinforced ultra-high temperature ceramic matrix composite material according to claim 1 or 2, characterized in that: The following steps are involved: S1. Dry-mixing silicon boron oxide nitrogen, pure silicon powder, zirconium diboride, a carbon source and the chopped fibers to obtain a composite raw material; S2. Loading the composite raw material into a mold for hot pressing and sintering to obtain the chopped fiber reinforced ultra-high temperature ceramic matrix composite material.
4. The preparation method according to claim 3, characterized in that: Step S1 specifically includes the following steps: Firstly, silicon boron oxide nitrogen, pure silicon powder, zirconium diboride and a carbon source are ball-milled and mixed to obtain a mixed powder; then, the mixed powder is stirred and mixed with the chopped fibers to obtain the composite raw material.
5. The preparation method according to claim 4, characterized in that: The mixing time of the ball milling is 3 to 4 hours, the material-to-ball ratio is 1:30 to 1:60, and the rotation speed is 120 to 160 rpm.
6. The preparation method according to claim 4, characterized in that: The stirring and mixing time is 8 to 12 hours.
7. The preparation method according to claim 3, characterized in that: The hot pressing sintering is specifically as follows: in a vacuum atmosphere, the temperature is raised to 1500-1800° C. at a rate of 5-10° C. / min, and then the temperature is kept at a uniaxial pressure of 20-40 MPa for 1-2 hours.
Citation Information
Patent Citations
Nitride ceramic-glass-ceramics composite material and preparation method thereof
CN105541340B
Preparation method for boron nitride fiber reinforced silicon boron oxygen nitrogen ceramic based composite material
CN110066176A
Carbon fiber reinforced silicon-boron-carbon-nitrogen-based ceramic composite material and preparation method thereof
CN113149680A
Continuous carbon fiber strengthening and toughening ultrahigh-temperature ceramic-based composite material and preparation method thereof
CN116444283A